Transcriptome Profiling of the Whitefly Bemisia tabaci MED in Response to Single Infection of Tomato yellow leaf curl virus, Tomato chlorosis virus, and Their Co-infection - Ding, Tian-Bo; Li, Jie; Chen, Er-Hu; Niu, Jin-Zhi; Chu, Dong (Frontiers in Physiology, 2019)
Tomato yellow leaf curl virus (TYLCV) and Tomato chlorosis virus (ToCV) are two of the most devastating cultivated tomato viruses, causing significant crop losses worldwide. As the vector of both TYLCV and ToCV, the whitefly Bemisia tabaci Mediterranean (MED) is mainly responsible for the rapid spread and mixed infection of TYLCV and ToCV in China. However, little is known concerning B. tabaci MED’s molecular response to TYLCV and ToCV infection or their co-infection. We determined the transcriptional responses of the whitefly MED to TYLCV infection, ToCV infection, and TYLCV&ToCV co-infection using Illumina sequencing. In all, 78, 221, and 60 differentially expressed genes (DEGs) were identified in TYLCV-infected, ToCV-infected, and TYLCV&ToCV co-infected whiteflies, respectively, compared with nonviruliferous whiteflies. Differentially regulated genes were sorted according to the roles in detoxification, stress response, immune response, transport, primary metabolism, cell function, and total fitness in whiteflies after feeding on virus-infected tomato plants. Alterations in the transcription profiles of genes involved in transport and energy metabolism occurred between TYLCV&ToCV co-infection and single infection with TYLCV or ToCV; this may be associated with the adaptation of the insect vector upon co-infection of the two viruses. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses demonstrated that the single infection with TYLCV or ToCV and the TYLCV&ToCV co-infection could perturb metabolic processes and metabolic pathways. Taken together, our results provide the initial foundation for exploring the molecular mechanisms of the response to TYLCV, ToCV single infection, and TYLCV&ToCV co-infection in B. tabaci MED, which will add to our knowledge of the interactions between plant viruses and insect vectors.